2007
DOI: 10.1007/s10618-007-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Data mining with Temporal Abstractions: learning rules from time series

Abstract: A large volume of research in temporal data mining is focusing on discovering temporal rules from time-stamped data. The majority of the methods proposed so far have been mainly devoted to the mining of temporal rules which describe relationships between data sequences or instantaneous events and do not consider the presence of complex temporal patterns into the dataset. Such complex patterns, such as trends or up and down behaviors, are often very interesting for the users. In this paper we propose a new kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 37 publications
(48 reference statements)
1
59
0
Order By: Relevance
“…We note that possible similar results could potentially be discovered with other approaches (e.g., temporal association rules with abstractions [16,36], or sequence mining [17,37]). Some of these intervalbased methods have been specifically extended to handle classification and prediction tasks, in particular, in clinical domains [38].…”
Section: Figuresupporting
confidence: 72%
“…We note that possible similar results could potentially be discovered with other approaches (e.g., temporal association rules with abstractions [16,36], or sequence mining [17,37]). Some of these intervalbased methods have been specifically extended to handle classification and prediction tasks, in particular, in clinical domains [38].…”
Section: Figuresupporting
confidence: 72%
“…This ontology, including the taxonomies describing temporal entities, data types, algorithms and temporal operators, is inspired by the temporal abstraction framework first presented in [4] and later formalized in [25]. With respect to this framework, two new concepts have been introduced, Aggregation and Combiner, both needed for reasoning with time intervals.…”
Section: Methodological Ontologymentioning
confidence: 99%
“…Then, a temporal data mining process can be applied to the abstract, interval-based concepts that are the output of the TA process; these interval-based concepts and the patterns that can be formed from them may have a more significant predictive value, and can be used for various data mining and classification tasks Sacchi et al 2007;Batal et al 2009) (indicated by (c2) in Fig. 1).…”
Section: Related Workmentioning
confidence: 99%